Experimental determination of the evolution of the incident heat flux received by a combustible during a cone calorimeter test: Influence of the flame irradiance. (March 2021) - Hermouet, Fabien; Guillaume, Éric; Rogaume, Thomas; Richard, Franck; El Houssami, Mohamad
The decomposition kinetic of polymeric materials in a cone calorimeter strongly depends on the irradiance level imposed at the sample's surface. Indeed, even if the irradiance level is supposed to be kept constant during cone calorimeter test, the amount of heat flux which is emitted by the flame can greatly increase the total heat flux received by the material. Analytical treatment on recently obtained results of an acrylonitrile-butadiene-styrene's mass loss rate with controlled atmosphere cone calorimeter has shown that the differences observed between well-ventilated and inert environments can be attributed to the impact of the flame. This observation has brought the necessity to determine the impact of the flaming process on the material thermal decomposition. To do so, series of experiments have been devised, based on the insertion of a heat fluxmeter within the matrix of an acrylonitrile butadiene styrene material, during cone calorimeter tests in order to measure the flame heat flux as a function of the decomposition and the combustion processes.